The two answers are the one selected and the choice |x-5| ≤ 1. The steps to solve the other equation are:
|x-5| ≤ 1
x-5 ≤ 1, x-5 ≥ 0
-(x-5) ≤ 6, x-5 is less than 0
x ≤ 6, x ≥ 5
x ≥ 4, x is less than 5
x ∈ [5,6]
x ∈ [4,5]
4 ≤ x ≤ 6
(^which was the original answer^)
The answer d)
Explaining
y = -18 + 3
y= -15
Answer: 7(m+2m) is equal to 7(m) + 7(2m)
Answer:
Step-by-step explanation:
Given expression is,
(2x - 1)² + 2(2x - 1) = (2x - 1)(2x + 1)
To prove this identity we will take the left hand side of the equation and will prove equal to the right side.
(2x - 1)² + 2(2x - 1) = (2x - 1)(2x + 1)
4x² - 4x + 1 + 4x - 2 = (2x - 1)(2x + 1)
4x² - 1 = (2x - 1)(2x + 1)
(2x - 1)(2x + 1) = (2x - 1)(2x + 1) [Since a² - b² = (a - b)(a + b)]